Tendencia de premiumización en el consumo sostenible. - Guzmán Armijos, Jonella Abigail; Gallegos Niola, Jimmy Gabriel; Moncada Roblez, Henry Junior; Benitez Luzuriaga, Francisco Vladimir (My University, 2021)
The diversity in the markets has allowed consumers to have varieties of products to choose from, where many of the companies have been directed to offer environmentally friendly goods or services and sustainable development, for this reason, customers have decided acquire healthy chemical-free products, standing out the premium articles that are made with high quality standards, therefore, this work aims to analyze the new trend of premiumization in sustainable consumption and the post-COVID-19 socioeconomic impact. The method that will be used It will be the hypothetical deductive method, through the collection of information using secondary sources. The results obtained are that people arewilling to pay a higher price for the premium product, which is always 20% higher than other products on the market; the applicants are young people who try to lead a more beneficial life. Finally, it is specified that consumers have been directed by organic products since they are healthy, ecological and sustainable, regardless of their price.
La diversidad en los mercados ha permitido que los consumidores tengan variedades de productos a elegir, en donde, muchas de las empresas se han direccionado por ofrecer bienes o servicios amigables con el medio ambiente y el desarrollo sostenible, por tal razón, los clientes han decidido adquirir productos saludables libres de químicos sobresaliendo los artículos premium que son elaborados con estándares de alta calidad, por ende, este trabajo tiene objetivo analizar la nueva tendencia de premiumización en el consumo sostenible y el impacto socioeconómico post COVID-19. El método que se utilizará será el método hipotético deductivo, a través de la recopilación de información utilizando fuentes secundarias. Los resultados obtenidos son que las personas están dispuestas a pagar un mayor precio por el producto premium, que siempre se mantienen con un 20% más elevado que los otros productos del mercado, los demandantes son personas jóvenes quienes tratan de llevar una vida más beneficiosa. Por último, se precisa que los consumidores se han direccionado por productos orgánicos puesto que son saludables, ecológicos y sostenibles, sin importar su precio.
Keywords: PREMIUMIZACIÓN; CONSUMO PREMIUM; CONSUMO SOSTENIBLE